Processing of Emotions in Speech in Forensic Patients With Schizophrenia: Impairments in Identification, Selective Attention, and Integration of Speech Channels - Leshem, Rotem; Icht, Michal; Bentzur, Roni; Ben-David, Boaz M. (Frontiers in Psychiatry, 2020)
Individuals with schizophrenia show deﬁcits in recognition of emotions which may increase the risk of violence. This study explored how forensic patients with schizophrenia process spoken emotion by: (a) identifying emotions expressed in prosodic and semantic content separately, (b) selectively attending to one speech channel while ignoring the other, and (c) integrating the prosodic and the semantic channels, compared to non-clinical controls. Twenty-one forensic patients with schizophrenia and 21 matched controls listened to sentences conveying four emotions (anger, happiness, sadness, and neutrality) presented in semantic or prosodic channels, in different combinations. They were asked to rate how much they agreed that the sentences conveyed a predefined emotion, focusing on one channel or on the sentence as a whole. Forensic patients with schizophrenia performed with intact identification and integration of spoken emotions, but their ratings indicated reduced discrimination, larger failures of selective attention, and under-ratings of negative emotions, compared to controls. This finding doesn’t support previous reports of an inclination to interpret social situations in a negative way among individuals with schizophrenia. Finally, current results may guide rehabilitation approaches matched to the pattern of auditory emotional processing presented by forensic patients with schizophrenia, improving social interactions and quality of life.